TINGKAT PENGETAHUAN TERHADAP OBAT GENERIK PADA MASYARAKAT KECAMATAN SIANTAR BARAT KOTA PEMATANG SIANTAR - Riahna Dewi Karina Brahmana; Arsiaty Sumule, Ismi N. Farida (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Generic drugs are drugs with the official name International Non-Proprietary Names (INN)which have been stipulated in the Indonesian pharmacopoeia or other standard books for the nutritious substances they contain. The problem that occurs in the community so far is that people still think that generic drugs are cheap drugs that are not of high quality. The purpose of this study was to determine the level of knowledge of generic drugs in Pematangsiantar City, Siantar Barat District.This research is included in the type of descriptive observational research with a cross sectional design. The respondents in this study were the people of Pematangsiantar City, Siantar Barat District, aged 17-65 years. The sampling technique used non-random sampling method. The instrument used in the form of a questionnaire, then analyzed descriptively. The data is presented in the form of tables, barcharts, and accompanied by a discussion.The level of knowledge of respondents about the definition of generic drugs, the benefitsof generic drugs, generic drug policies, classification of generic drugs, and the quality of generic drugs is mostly in the good category with the percentages of 73%, 55%, 59%, 69%, 63% respectively.